Machine learning approach for improving decision support in ICU - Siddiquee, Mohib Billah; Fuad, Mostofa Jamil; Azmain, Md. Fahim (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.